Analysing literacy engagement from a sociocultural perspective: appropriating an assessment tool - Marilyn Kell, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Qualitative research broadens and extends notions of valid data. For example, when the researched are vulnerable and there are no baseline data, how can valid claims about the participants be made? The data described in this paper derives from a study of nine men who self-reported literacy difficulties. As highly vulnerable participants no data could be obtained from their worksites, nor was the researcher prepared to subject them to an assessment instrument. Ongoing interviews over more than one year were the predominant source of data.The task for the researcher was to somehow make sense of hours of interesting interviews.'Using three case studies from a doctoral thesis (Kell, 2005) this paper demonstrates how appropriating an instrument designed for another purpose and transforming it into an instrument of analysis can expose literacies that are not apparent in standard tests. The instrument, Communication collaboration and culture: The national framework of adult English language,literacy and numeracy competence (Cope, Kalantzis, Luke, McConnack, Morgan, Slade, Solomon & Veal, 1995) was originally written to assist adult literacy and numeracy teachers in Australia assess the literacy skills of adults in order to plan individual teaching programs. The value of this instrument was that it is premised on the broad literacy and numeracy requirements of the contemporary workplace and on the notion that "competence is context-specific, and reflects larger social, cultural and economic agendas" (1995, p. 41). In a study that took a sociocultural perspective, the appropriation of an instrument such as this as the analytical tool seemed to be particularly apt.